Connections I : a cognitive approach to intermediate Chinese - Liu, Jennifer Li-chia, 1964- (Chinese in context language learning series., 2004)
Praise for Interactions I & II: "Practical and lively without neglecting the structure and the writing system. The workbook is especially interesting and helpful." 'Chauncey C. Chu, University of Florida "... by far the best first-year textbooks available." 'Sabina Knight, Smith College Connections I & II is the second-year sequence to accompany the enormously popular introductory texts Interactions I & II by Margaret Yan and Jennifer Li-chia Liu. This innovative system makes learning Chinese an interactive, cognitive process rather than a matter of simple rote or drill. Connections is designed to offer intermediate learners of Chinese a complete set of learning tools to improve their language skills and enhance their understanding of Chinese culture and society. Lesson topics revolve around everyday themes and real-world communication among four central characters'a mainland Chinese, a Taiwanese, a Chinese American, and a non-Chinese American'familiar to students using Interactions. Each 10-chapter volume is accompanied by a workbook. Chapters include sections on vocabulary, text, mini-dialogue, characters, grammar, and culture notes, accompanied by engaging graphics. Connections also includes stories and songs, and makes use of a wide variety of texts such as narrative, dialogue, journal entries, riddles, jokes, news headlines, and lyrics.